ANALYSIS OF DIFFERENCES IN CONSUMPTION LEVELS BETWEEN GENERATION Y AND GENERATION Z INFLUENCED BY DIGITALIZATION, SOCIAL FACTORS, AND DEMOGRAPHIC CHARACTERISTICS - Awaluddin Siahaan; Fitrawaty; Indra Maipita (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of digitalization and social factors on consumption levels among Generation Y and Generation Z by considering generational and demographic characteristics as moderating variables. The study employed a quantitative approach using primary data collected through questionnaires distributed to 200 respondents in Medan City. Likert-scale data were transformed from ordinal to interval scales using the Method of Successive Intervals (MSI). Data analysis was conducted using the Moderated Multiple Regression (MMR) method to examine the direct effects of the independent variables and the moderating roles of generational and demographic variables. The results indicate that digitalization and social factors have a positive and significant effect on consumption levels. Generational and demographic variables also exert a positive and significant influence on community consumption levels. However, the moderation analysis reveals that neither generation nor demographic characteristics moderate the relationship between digitalization and social factors and consumption levels. These findings suggest that the effects of digitalization and social factors on consumption are relatively consistent across different generational and demographic groups. This study confirms that digitalization is a dominant factor influencing consumer behavior in the digital economy era, supported by social environmental influences as well as generational and demographic characteristics. Keywords: Consumption Level, Digitalization, Social Factors, Generation, Demographics.